Generation and Characterization of Torudokimab (LY3375880): A Monoclonal Antibody That Neutralizes Interleukin-33 - Okragly AJ (Dove Medical Press, 2021)
Angela J Okragly,1 Katie Brannon Corwin,2 Marikka Elia,3 Dongmei He,3 Oliver Schroeder,3 Qing Zhang,3 Tatiyana Shiyanova,2 Stuart Bright,1 Sarah B Dicker,4 Lukasz Chlewicki,4 Stephanie ME Truhlar,3 Julian Davies,3 Chetan N Patel,2 Robert J Benschop1 1Immunology Research, Eli Lilly and Company, Indianapolis, IN, USA; 2BioTechnology Discovery Research, Eli Lilly and Company, Indianapolis, IN, USA; 3BioTechnology Discovery Research Eli Lilly and Company, San Diego, CA, USA; 4ADME, Eli Lilly and Company, Indianapolis, IN, USACorrespondence: Angela J OkraglyImmunology Research, Eli Lilly and Company, Lilly Corporate Center, Indianapolis, IN, 46285, USATel +1- 317-276-2839Email okragly_angela@lilly.comBackground: Interleukin-33 (IL-33) is an alarmin that is released following cellular damage, mechanical injury, or necrosis. It is a member of the IL-1 family and binds to a heterodimer receptor consisting of ST2 and IL-1RAP to induce the production of a wide range of cellular mediators, including the type 2 cytokines IL-4, IL-5 and IL-13. This relationship has led to the hypothesis that the IL-33/ST2 pathway is a driver of allergic disease and inhibition of the IL-33 and ST2 association could have therapeutic benefit.Methods: In this paper, we describe the selection of a phage antibody through the ability to bind human IL-33 and block IL-33/ST2 interaction. This hit antibody was then affinity matured by site-directed mutagenesis of the antibody complementarity-determining regions (CDRs). Further characterization of a fully human monoclonal antibody (mAb), torudokimab (LY3375880) included demonstration of human IL-33 neutralization activity in vitro with an NFκB reporter assay and IL-33 induced mast cell cytokine secretion assay, followed by an in vivo IL-33-induced pharmacodynamic inhibition assay in mice that used IL-5 production as the endpoint.Results: Torudokimab is highly specific to IL-33 and does not bind any of the other IL-1 family members. Furthermore, torudokimab binds human and cynomolgus monkey IL-33 with higher affinity than the binding affinity of IL-33 to ST2, but does not bind mouse, rat, or rabbit IL-33. Torudokimab’s half-life in cynomolgous monkey projects monthly dosing in the clinic.Conclusion: Due to torudokimab’s high affinity, its ability to completely neutralize IL-33 activity in vitro and in vivo, and the observed cynomolgus monkey pharmacokinetic properties, this molecule was selected for clinical development.Keywords: IL-33, Th2 immune response, monoclonal antibody